The Internal Branding Process: Customer Reprofiling and Brand Positioning (Empirical Study on Traditional Snack Food in Bandung-Indonesia) - Dagustani, Dani; Buchory, Herry A; Satya, Mutia T; Diryana, Ivan (International Journal of Business, Economics and Management, 2016)
Currently the target market traditional snack food called “borondong”of Majalaya-Bandung only based on geographic region, with the target market in several areas around Bandung. This situation cause the product looks almost same or a generic product in the consumers perspective that have difficulties to position its brand excellence in consumer perceptions. On the other hand the customer profile of target market is very diverse both in terms of demographics, lifestyle andbehavior. Advantages that are not understood by the consumer will certainly have an impact on the marketing performance of traditional snack food businesses like “borondong” .The purpose of this study was to conduct re-profile consumer snacks food Borondong which is based on differences existing products, demographics and consumer behavior. Results of re-profile customer and the target markets which appropriate for each brand of products is the basis of brand positioning of each product. This research was conducted with descriptive method through surveys descriptive and data analysis using cluster analysis and corespondence analysis and product profile mapping techniques. Results of the research, cluster analysis to form six new segment of the consumer market Borondong, which is the cash cow, the next new hope, the good boy, poor segments, Nice Niche Market and challenging targets. Correspondence analysis resulted in correspondence between the brand with a new positioning attributes.